Target Costing for Production Cost Efficiency at Tongkat Mas Brem Factory - Safera Nurhaliza; Anna Isrowiyah; Ari Kamayanti (Niqosiya: Journal of Economics and Business Research, 2025)
Introduction: This study aims to optimize the application of target costing to increase production cost efficiency and thereby increase company profits. Research Methods: The object of this study was the Brem Tongkat Mas factory in Kaliabu Village, Sumberejo, Mejayan District, Madiun Regency. This type of research was applied research using descriptive qualitative approach with sources derived from interviews, observations, and documentation. Results: The results showed that the application of target costing was able to increase the company's production cost efficiency by 4.30%. This can be done using alternative value engineering to analyze costs by paying attention to their efficiency and effectiveness to maintain the sustainability of the company. In conducting value engineering, it is possible to find cheaper suppliers of sticky rice raw materials and overhead materials for wood fuel factories. Conclusion: By optimizing the application of target costing can help companies achieve their expected profits without compromising product quality.